Urinary Tract Infection in Febrile Children Attending OPD at Seti Zonal Hospital - Sharma, Kamal Raj; Amgain, Kapil; Sharma, Upama; Sharma, Anupama (Journal of Karnali Academy of Health Sciences, 2019)
Background: Urinary tract infection is a common problem in febrile children. It is dangerous because it may lead to a life-threatening episode or may lead to renal scarring. Recurrence of UTI is common in children. Though it is a serious problem, it is treatable if diagnosed early. Methods: A total of 340 urine samples from pediatric patients attending pediatric OPD were sent for culture after medical history taking, physical examination and counselling parents/guardians/children. Besides fever other presenting complains were noted. Results: In total there were 340 samples, 127 (37.35%) samples were culture positive showing isolated bacterial growth and 53 (15.6%) showed mixed bacterial growth in the culture. Out of 127 culture positive urine samples, 51.2% showed growth of E. Coli, followed by Proteus spp. and Streptococcus fecalis. Other less common bacteria were Klebsiella, Staphylococcus and Enterobacter spp. More than half 75(59.05%) of the children were male and only 52(40.95%) were female. Similarly, male children (59.06%) were affected more than female children (40.94%). Apart from fever, 72 (56.7%) of the children were presented with the symptoms of feeding problems, 68 (53.5%) were presented with pain abdomen, and 65 (51.2%) were presented with vomiting. Less typical presenting symptoms of the children with UTI were screaming attacks/irritability (37.8%), dysuria (30.0%) and frequency of urination (24.4%). Similarly, non-specific symptoms like diarrhea, failure to thrive, and convulsion were present in few children and none of the children had enuresis and loin pain. Of all the urine culture positive cases the bacterial isolate was Escherichia coli Conclusion: Prevalence of UTI was more in male than in female children and E. coli was found to be the most common bacteria causing it. Besides fever, feeding problems, pain abdomen, and vomiting were the major presenting symptoms of morbidity in children with UTI. Although UTI is rarely a difficult problem, for the accurate diagnosis of UTI in children attention should be paid during the history taking and collection of the urine sample.